Research Carried out to Improve the Efficiency of Dust Capture Equipment in Cotton Cleaning Enterprises (Texas Journal of Engineering and Technology, 2023)
pollution of atmospheric air with various industrial waste and other substances ultimately threatens the life of living beings in land and water bodies in the biosphere. Such mixtures in the air gradually sit on the surface of the Earth, showing a great obstacle to the growth and development of plants.